1996
DOI: 10.1007/s0021663550909
|View full text |Cite
|
Sign up to set email alerts
|

Applications of laser-induced breakdown spectrometry (LIBS) in surface analysis

Abstract: The applicability of laser-induced breakdown spectrometry (LIBS) for surface analysis is presented in terms of its lateral and depth resolution. A pulsed N(2) laser at 337.1 nm (3.65 J/cm(2)) was used to irradiate solar cells employed for photovoltaic energy production. Laser produced plasmas were collected and detected using a charge-coupled device. An experimental device developed in the laboratory permits an exact synchronization of sample positioning using an XY motorized system with laser pulses. Multiele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 16 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…The potential of the LIBS for the characterization and chemical mapping of surfaces has been demonstrated [4][5][6][7][8][9][10][11][12][13][14][15][16]. LIBS presents the advantages of performing analysis in few seconds, allowing direct sampling from any material irrespective of its conductive status in air atmospheric pressure, simplifying the analytical sequence by minimizing and/or avoiding sample preparation steps, and presenting no limitations or minimum restrictions regarding to sample size [4,16].…”
Section: Introductionmentioning
confidence: 99%
“…The potential of the LIBS for the characterization and chemical mapping of surfaces has been demonstrated [4][5][6][7][8][9][10][11][12][13][14][15][16]. LIBS presents the advantages of performing analysis in few seconds, allowing direct sampling from any material irrespective of its conductive status in air atmospheric pressure, simplifying the analytical sequence by minimizing and/or avoiding sample preparation steps, and presenting no limitations or minimum restrictions regarding to sample size [4,16].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the conventional LIBS system, the laser focusing optical path generally integrates an optical microscope system, which is mainly used for tight focusing of the laser beam and magnification observation of the sample analysis area. In practical applications, in order to obtain smaller focal spots and improve the resolution of the ablative crater, in the optical path design, one aspect would reduce the divergence angle of the laser and improve the quality of the beam through the laser shaping and beam expanding system [75,76] ; on the other hand, the laser beams is focused by the microlens with short focus.…”
Section: Optics Systemmentioning
confidence: 99%
“…532 7 ns 2.2 mJ 20 µm University of santander [82] Pb, Si, Cu sheet Pb, Si, Cu, etc. 1064 550 ps 7 µJ 10-15 µm University of Florida [65] [76] Si film Si 343+355 500 fs + 6 ns < 2 µm Ocean University of China [74] Printed circuit board Cu 532 10 ns 5 mJ 25 µm Northern Illinois University [90] Fluid Na 266 10 ns 200 μJ 10 µm 60 ppm University of Alberta [2] Paper Ca, Si, etc. 193 10 ns 100 µm University of Jyvaskyla [92] SUN Lan-Xiang et al / Chinese Journal of Analytical Chemistry, 2018, 46(10): 1518-1527…”
Section: Stainless Steel Hp-40mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1996, it was demonstrated that LIBS is a useful technique to carry out surface analysis by studying a silicon solar cell [13]. Ultrafast laser ablation was introduced to study ex situ chemical compositional variations of the solid electrolyte interphase layer and proved the advantage of LIBS in interfacial phenomena of battery systems [14].…”
Section: Introductionmentioning
confidence: 99%